Churchyard Memorials of Peebles, Stobo, Lyne, West Linton, and Newlands (Proceedings of the Society of Antiquaries of Scotland, 1913)
In the parish burial ground of Peebles, the tombstones are very numerous, the older among them presenting several symbolic renderings that are of considerable beauty\r and importance. Most of them, however, are of the type common to Lowland churchyards. One eighteenth century example has a skull and cross-bones surmounted by an hourglass, the legends Memento Mori and Fugit Hora. Another includes a cherub head, and two serpents twining round a pole surmounted by a dove. The quality of design in the nineteenth-century examples is not as well executed. Numerous table tombs are also described. Many of similar style are present at Stobo and Lyne. At West Linton the lower portion of an ancient grave-cover, whose ornamentation\r includes a nail-head border and a pair of shears survives. A stone at West Linton depicts a set of miner's tools. A grave slab at Newlands commemorating an ecclesiastic has only a single incised chalice.